Probable rainfall in Lambari region, Southern Minas Gerais State - Pinto, Leandro Campos; Lima, Pedro Luiz Terra; Silveira, Sílvio de Castro; Muniz, Joel Augusto; de Souza, Zélio Resende; de Mello, Carlos Rogério (Revista Agrogeoambiental, 2015)
The knowledge of rainfall distribution and behavior at certain area is indispensable at irrigation systems design and management, as well rainfall tracking regarding soil conservation aspects. Thus the objective of this research was the comparison and statistical adequacy of probability distribution models applied to probable rainfall studies, to determine which probability model is more appropriate to distinct seasons (monthly, fortnightly and decendial) and to estimate probable rainfall for different probability levels on Lambari region, South of Minas Gerais state, Brazil. Log-normal at 3 parameters and Gamma were the most adequate for monthly and decendial periods, for fortnight periods Gamma was the most adequate, with annual average values of monthly, fortnightly and decendial rainfall to 75% probability level of 82.4, 72.1, and 42.4 mm, respectively.